Intensity of media and impulse buying. - Choo, Hui Ling. (2008)
This research paper outlines an exploratory study of how the intensity of media elicits emotional responses that affect consumers’ buying behaviour in the Singapore context. According to a research study done by Aledaar et al. (2003), intensity of media refers to the way people process information; i.e., the more cognitive resources used in processing a certain piece of information or media form, the higher is the intensity of the information or media form.